Bilateral and positional differences in abdominal muscle thickness of golfers with a history of low back pain - Skibski, A.; Callahan, E.; Stout, J. R.; Ingersoll, C. D.; Mangum, L. C. (International Journal of Athletic Therapy & Training, 2025)
Low back pain is a frequent injury in golfers which impacts trunk muscle activity patterns. The primary purpose of this study was to bilaterally compare thickness of the external obliques and internal obliques across three positions (supine, golf setup, and swing peak) in 16 adult golfers with a history of low back pain via ultrasound. There were no significant differences between lead and trail external obliques thickness in supine (Z = 0.982, p = .326), setup (Z = 1.758, p = .079), or peak (Z = 1.396, p = .163). There were no significant differences between lead and trail internal obliques thickness in supine (Z = 1.448, p = .148), setup (Z = 0.078, p = .938), or peak (Z = 1.086, p = .278). Golfers with a history of low back pain do not demonstrate asymmetrical oblique adaptations.